Cucurbitacins Elicit Anti-Platelet Activity via Perturbation of the Cytoskeleton and Integrin Function - Kriek, Neline; Nock, Sophie H.; Sage, Tanya; Khalifa, Badrija; Bye, Alexander P.; Mitchell, Joanne L.; Thomson, Steven; McLaughlin, Mark G.; Jones, Sarah; Gibbins, Jonathan M.; Unsworth, Amanda J. (Thrombosis and Haemostasis, 2022)
Cucurbitacins are dietary compounds that have been shown to elicit a range of anti-tumour, anti-inflammatory and anti-atherosclerotic activities. Originally identified as signal transducer and activator of transcription, STAT, inhibitors, a variety of mechanisms of action have since been described, including dysregulation of the actin cytoskeleton and disruption of integrin function. Integrin outside-in signalling and cytoskeletal rearrangements are critical for the propagation of stable thrombus formation and clot retraction following platelet adhesion at the site of vessel damage. The effects of cucurbitacins on platelet function and thrombus formation are unknown. We report for the first time anti-platelet and anti-thrombotic effects of cucurbitacins B, E and I in human platelets. Treatment of platelets with cucurbitacins resulted in attenuation of platelet aggregation, secretion and fibrinogen binding following stimulation by platelet agonists. Cucurbitacins were also found to potently inhibit other integrin- and cytoskeleton-mediated events, including adhesion, spreading and clot retraction. Further investigation of cytoskeletal dynamics found treatment with cucurbitacins altered cofilin phosphorylation, enhanced activation and increased F actin polymerisation and microtubule assembly. Disruption to cytoskeletal dynamics has been previously shown to impair integrin activation, platelet spreading and clot retraction. Anti-platelet properties of cucurbitacins were found to extend to a disruption of stable thrombus formation, with an increase in thrombi instability and de-aggregation under flow. Our research identifies novel, anti-platelet and anti-thrombotic actions of cucurbitacins that appear to be linked to dysregulation of cytoskeletal dynamics and integrin function.
Keywords: thrombosis; platelet; cytoskeleton; cucurbitacins; signalling